Determinants of adoption of improved cassava varieties among farming households in Oyo, Benue, and Akwa Ibom states of Nigeria - Tahirou, Abdoulaye; Bamire, A.S.; Oparinde, Adewale; Akinola, A.A. (International Food Policy Research Institute, 2015)
Biofortified pro-vitamin A cassava varieties are being developed and deployed in Nigeria and other countries. Understanding the adoption pathways of already released non-biofortified improved cassava varieties can inform decision makers on how best to disseminate the newly developed varieties. This paper empirically investigated factors influencing adoption of the improved cassava varieties in Akwa Ibom, Benue, and Oyo states in Nigeria. A multi-stage sampling technique was used to select a sample of 1,609 farming households. Data were analyzed using descriptive statistics and the Probit regression model. The results* showed that Oyo State had the highest reported rate of improved cassava use (69 percent of farmers surveyed), followed by Benue (52 percent), with the lowest in Akwa Ibom (38 percent). The variables that significantly influenced adoption of improved cassava varieties include education (p<0.01), livestock ownership (p<0.05), access to extension services (p<0.01), farmers’ organizations (p<0.05), participation in demonstration trials, and location-specific variables (p<0.01). The positive influence of the location-specific variable in favor of Oyo compared with Benue could be linked to proximity to, and the activities of, international and national research institutes. Within states, regression analysis reveals significant differences across agricultural extension zones. This suggests the need to develop localized strategies that account for applicable socioeconomic and institutional conditions. To increase adoption, an intensive program for farmers’ participation in on-farm demonstration trials should be considered. This can be achieved by facilitating group formation to encourage increased knowledge sharing among members, thereby promoting uptake of newly developed pro-vitamin A cassava varieties.